PENGARUH SISTEM HUKUM TERHADAP MANAJEMEN LABA DENGAN MEKANISME CORPORATE GOVERNANCE SEBAGAI VARIABEL PEMODERASI (Studi pada Perusahaan Industri Barang Konsumsi yang Terdaftar di Bursa Efek Indonesia dan Bursa Malaysia) - Mayapada, Arung Gihna (Katalogis, 2017)
The purpose of this research is to analyze the effect of legal systems on earnings management and the effect of legal systems on earnings management moderated by managerial and institutional ownerships as the part of corporate governance mechanism. This research covers two countries which are Indonesia representing civil law country and Malaysia representing common law country. This research period is from year 2012 until year 2015. The data are obtained from corporation annual reports which are available in official site of Bursa Efek Indonesia and Bursa Malaysia. The hypotheses testing techniques used in this research are multiple regression analysis, independent sample T test and residual test. The result of multiple regression analysis shows that legal systems have significance effect on earnings management. The independent sample T test shows that there is a significance difference between earnings management degree in Malaysia corporations with Indonesia corporations, which earnings management degree of Malaysia corporations with common law are lower than earnings management degree of Indonesia corporations with civil law. While, the residual tests show that managerial and institutional ownerships are not moderating variables on the relationship of the effect of legal systems on earnings management.